2011
DOI: 10.1257/aer.101.3.60
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bottle Laws on Income: New Empirical Results

Abstract: Eleven U.S. states have "bottle laws", deposit-refund programs that combine a consumption tax with a recycling rebate. When states set the bottle deposit low enough it becomes a tax on high wage earners, for whom the opportunity cost of their time prevents them from returning containers for their deposit. However, this bottle deposit will still be high enough that harvesting recyclables provides employment for low wage earners.Using individual data on observed cash recycling behavior, this paper shows that an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…Waste pickers collect, bundle and sell their materials to buyers in both formal and informal markets who trade wastes as commodities. This is a highly imitable business model with little skill required and few barriers to entry (see, e.g., Ashenmiller, ). In developing nations it can be a highly competitive activity with many new entrants (Njoroge et al ., ), and typically has a capped income unless value is added through other activities such as dismantling e‐wastes or conversion to other products (Oteng‐Ababio, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste pickers collect, bundle and sell their materials to buyers in both formal and informal markets who trade wastes as commodities. This is a highly imitable business model with little skill required and few barriers to entry (see, e.g., Ashenmiller, ). In developing nations it can be a highly competitive activity with many new entrants (Njoroge et al ., ), and typically has a capped income unless value is added through other activities such as dismantling e‐wastes or conversion to other products (Oteng‐Ababio, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…However, earning an income from collecting waste is not just a developing world phenomenon. In many US states deposit‐refund programmes are used as an economic trigger to promote recycling – offering opportunities for low‐wage earners to pick the recyclables from garbage and generate income (Ashenmiller, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…One of the impediments to accurate measurement is that scavenging is generally illegal and is practiced informally and covertly by individuals with limited economic means. Ashenmiller (2011) found that, among households participating in a Santa Barbara, California study, beverage deposit scavenging is a significant source of income for those in the lowest income bracket. In New York City, individuals scavenge recycling containers to collect revenues from aluminum, scrap metal, and other commodities, which include redeemable containers (Lange, 2012).…”
Section: Generating Curbside Recycling Related Littermentioning
confidence: 99%
“…In practice, within the European Union alone, the majority of states employ volume-based schemes, although several do use weight-based schemes or a combination of systems including frequency-based schemes (Watkins et al, 2012). While differentiated charging of mixed/recycled waste has occupied centre-stage in both theory and practise, the design of alternative incentives (like deposit-refund schemes) has also received some attention (see for instance, Ashenmiller, 2011). An insightful overview of the distinctions between advance disposal fees, recycling subsidies and deposit-refund schemes (in a producer context) is provided in Palmer et al (1997), who find evidence for the latter as the least-cost option (Palmer et al, 1997).…”
Section: Chargesmentioning
confidence: 99%